Sistema para la toma de datos en pruebas regionales de yuca - Toro, Julio C.; Canas, A.; Granados, E. (International Center for Tropical Agriculture, 1983)
A system for data recording, based on the experience obtained with regional trials at the Centro internacional de Agricultura Tropical during 7 yr, is given. This system uses time advantageously by simplifying data recording and by computerizing analysis; errors in information management and transcription are thus avoided. The information obtained in these trials within each country and at an international level is also synthesized, making its use easier. The 8 basic records are: general data of the locality; soil analysis; establishment of the crop; distribution in the field; germination, weed control; pests, diseases, and edaphic problems; data on harvest; and daily precipitation. Instructions on how to fill out the records are included along with tables for pest and disease evaluation. (CIAT)